Electroencephalographic pattern between high cognitive and low cognitive brains - Namrata Upadhayay; Rita Khadka; Bishnu Hari Paudel (Al Ameen Medical College, 2017)
Background: The brain electrical activity can vary according to the types of tasks, quality of individuals (brilliant or dull) and state (resting/exercise) of the body. Objectives: To compare the effect of educational course on electroencephalogram (EEG) between the high and the low cognitive medical students. Methods: Eighty three students were enrolled in the study. Fifty nine students scored high and 24 students scored less in the cognitive test. The EEG was recorded at the start and end of the first year course. It was recorded in an eye-closed state for 5-minutes. Data was subjected to frequency power analysis. Comparison between the groups and within the groups were done by Mann-Whitney U test (p<0.05). Results: At the course-start or at the course-end, theta and alpha1 activities were higher at many EEG sites in the low cognitive students (CS) as compared to the high CS. However, two groups showed similar change in EEG pattern on comparing between the two visits. All EEG powers (alpha1, alpha2, theta, and delta) at maximum brain areas were less at the course-end as compared to the course-start in both the groups; except prefrontal alpha1 and theta activities. Peculiarly, only in the low CS beta activity was less in the course-end as compared to the course-start. Conclusion: Brain neuronal activity showed similar EEG pattern change in two different cognitive groups. At the course-end, brain became more efficient (less EEG power) as compared to the course-start in both the groups. However, throughout the year, the low CS had higher EEG power (theta and alpha1) and is in stress (high beta-start of course) as compared to the high CS. Hence, efficient and trained brain has less EEG powers at rest.